Implikasi Alih Fungsi Lahan menjadi Destinasi Wisata di Sekitar Cafe Sawah Desa Pujon Kidul - Rafi Alfiansyah; Pratiwi Noersyah Bani; Vina Salviana Darvina Soerdarwo (Jurnal Sosiologi Andalas, 2022)
The conversion of agricultural land into a tourist destination occurred in Pujon Kidul Village, Malang Regency. These changes have occurred since the emergence of Sawah Cafe tourism, so that it has implications for the occurrence of risks in the form of land conversion from the agricultural sector to become tourist destinations (such as ATV rides, motorbikes, cafes, homestays, restaurants, parking lots and shops). In addition, it also has an impact on the pattern of community life (especially around Cafe Sawah). This study uses qualitative methods, the type of descriptive research. Data collection techniques used are observation, interviews, and document studies. The results showed that the community carried out commodification, in the form of land conversion from agriculture to tourism because the income factor was more promising and the economy increased, so it had implications for the social, economic and environmental aspects of the local community. But on the other hand it poses a risk in the form of social inequality and competition, environmental damage will occur due to increased air and water pollution, decreased quality of the surrounding environment due to garbage around tourism development areas and traffic jams.